2004
DOI: 10.1111/j.0956-7976.2004.00710.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Racial Diversity on Complex Thinking in College Students

Abstract: ABSTRACT-An experiment varying the racial (Black, White) and opinion composition in small-group discussions was conducted with college students (N 5 357) at three universities to test for effects on the perceived novelty of group members' contributions to discussion and on participants' integrative complexity. Results showed that racial and opinion minorities were both perceived as contributing to novelty. Generally positive effects on integrative complexity were found when the groups had racialand opinion-min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
262
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 424 publications
(278 citation statements)
references
References 10 publications
12
262
1
3
Order By: Relevance
“…Research has praised social category diversity's positive benefits for group performance (Antonio et al 2004;McLeod et al 1996;Sommers 2006;Sommers et al 2008), while lamenting its negative impact on interpersonal relationships. Our findings suggest that in decision-making situations, rather than lamenting the relatively lower levels of interpersonal attraction in diverse groups compared to homogeneous groups, we may want to lament the higher levels of interpersonal attraction in homogeneous groups for their detrimental impact on cognition and performance (Phillips and Apfelbaum 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Research has praised social category diversity's positive benefits for group performance (Antonio et al 2004;McLeod et al 1996;Sommers 2006;Sommers et al 2008), while lamenting its negative impact on interpersonal relationships. Our findings suggest that in decision-making situations, rather than lamenting the relatively lower levels of interpersonal attraction in diverse groups compared to homogeneous groups, we may want to lament the higher levels of interpersonal attraction in homogeneous groups for their detrimental impact on cognition and performance (Phillips and Apfelbaum 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Structural diversity is most beneficial when an institution also promotes high levels of cross-racial interaction. These interactions are related to students' growth in a variety of areas, including critical and active thinking (Gurin, 1999;Gurin et al, 2002;Nelson Laird, 2005;Pascarella et al, 1996), perspective taking (Hurtado, Engberg, & Ponjuan, 2003;Hurtado, 2005), pluralistic orientation (Engberg, 2006, Jayakumar, 2008, leadership skills (Antonio, 2001;Jayakumar, 2008), cultural awareness and understanding (Antonio, 2001;Astin, 1993aAstin, , 1993bChang, 1996;Milem, 1994), reduced racial bias (Denson, 2009;Pettigrew & Tropp, 2006), civic values or interest (Chang, Astin, & Kim, 2004;Gurin et al, 2002), academic and social self-concept (Chang, 1999;Gurin et al, 2002), complex thinking (Antonio et al, 2004), and cognitive development (Antonio et al, 2004;Astin, 1993aAstin, , 1993bBowman, 2010;Gurin et al, 2002;Hurtado, 2001Hurtado, , 2005.…”
Section: Diversity Literaturementioning
confidence: 99%
“…The vast literature supporting the educational benefits of racial diversity demonstrates the value of campus diversity infrastructures on a wide range of outcomes (e.g., Gurin, Hurtado, Dey, & Gurin, 2003), including cognitive development (e.g., Antonio et al, 2004;Bowman, 2010), academic and social self-concept (e.g., Chang, Denson, Sáenz, & Misa, 2006;Denson & Chang, 2009), leadership skills and cultural awareness (e.g., Antonio, 2001;Jayakumar, 2008), civic development (e.g., Bowman, 2011), prejudice reduction (e.g., Davies et al, 2011;Jayakumar, 2009), and preparation for an increasingly diverse 21st-century workforce (e.g., Engberg & Hurtado, 2011;Gurin, Nagda, & Lopez, 2004;Page, 2009).…”
mentioning
confidence: 99%
“…For example, law schools may encourage students to form discussion groups with peers whose viewpoints are known to differ from their own. This particular technique was used in an experimental study conducted by Antonio et al (2004), who found that undergraduate students who were randomly assigned to racially diverse focus groups developed a higher degree of integrative complexity in their perspectives on an array of issues compared with the racially homogenous groups. This study shows that a similar type of effect generalizes to a large-scale, longitudinal study of naturally occurring law school interactions inside and outside of the classroom; students who have more frequent encounters with diverse peers rate their educational experience being more intellectually varied and open.…”
Section: Substantive Conclusion and Implicationsmentioning
confidence: 99%
“…This study was motivated by an issue of contemporary relevance in the legal system: the benefits of educational diversity (Gratz v. Bollinger, 2003;Grutter v. Bollinger, 2003;Meredith v. Jefferson Co. Board of Education, 2007;Parents v. Seattle, 2007). Theory and previous empirical research suggest that increased levels of racial diversity within a school improve student outcomes by (a) reducing prejudiced attitudes and (b) increasing students' exposure to a variety of viewpoints (i.e., diversity of ideas; Antonio, 2001;Antonio et al, 2004;Bowen & Bok, 2000;Chang, Denson, Sáenz, & Misa, 2006;Gurin, Dey, Hurtado, & Gurin, 2002;Holzer, Neumark, & Besharov, 2006;Niemann & Maruyama, 2005). The effects of racial diversity are thought to be mediated by intergroup contact with peers ("contact theory"; Allport, 1954).…”
mentioning
confidence: 99%